The Finnish Great Depression of the 1990s: Soviet Trade or Home-Made? - Tero Kuusi (The Research Institute of the Finnish Economy (ETLA), 2015)
This paper reconsiders the reasons for the Finnish Great Depression.The paper argues that during the crisis Finland experienced institutional adjustments that are largely neglected by the current literature, and argues that both financial and tax shocks may have contributed to the crisis more than it has been previously suggested. It is shown by using a general equilibrium model that together these factors can generate a large and widespread fall in key macroeconomic variables, whereas the results suggest that the direct impact of the collapse of the Soviet Union may not have been as large as suggested before.
Keywords: 330